Examination of age- and sex-related changes in protein expression within the hippocampus and prefrontal cortex during withdrawal from a subchronic history of binge-drinking in C57BL/6J mice - Jimenez Chavez, C. Leonardo; Madory, Lauren E.; Denning, Chris J. E.; Lee, Edward C.; Nguyen, Dylan T.; Scheldrup, Gavin P.; Szumlinski, Karen K. (Frontiers in Behavioral Neuroscience, 2025)
IntroductionEarly-onset binge-drinking and biological sex are critical risk factors for the development of cognitive decline and neurodegeneration associated with Alzheimer’s disease and related dementias (ADRDs). Recently, we demonstrated that a prior history of binge-drinking during adolescence induces what appears to be latent (>6 months post-drinking) changes in the expression of glutamate receptors and neuropathology markers within brain regions governing working and spatial memory, many of which precede the manifestation of overt cognitive anomalies.MethodsTo determine whether alcohol-induced changes in protein expression manifest within the hippocampus and prefrontal cortex at earlier times post-drinking, we conducted immunoblotting on tissue from mice with a subchronic history of binge-drinking (14 days of 2-h access to 10, 20 and 40% ethanol) during either adolescence or adulthood.ResultsWe previously reported that this binge-drinking regimen produces mild, age- and sex-selective, changes in working memory and spatial recall when behavior was assayed starting a 1 or 30 days withdrawal. Here, we provide evidence a subchronic binge-drinking history is sufficient to alter the expression of certain glutamate receptors and ADRD-related proteins during the first few months following drinking cessation. Further, these alcohol-induced protein changes are regionally specific and sex-selective.DiscussionThe present results add to our growing understanding of the long-term consequences of adolescent-onset binge-drinking of potential relevance to understanding individual variability in the cognitive consequences of heavy drinking.